FRACTURAS DE LA IDENTIDAD EN LA FORMACIÓN POR COMPETENCIAS DE LOS FUTUROS PROFESORES: ANÁLISIS DE UNA EXPERIENCIA - Galaz, Alberto Galaz (Revista de Pedagogía, 2015)
El enfoque por competencias se ha convertido en una atrayente pero compleja alternativa para las instituciones que buscan mejorar la formación de sus profesores dado que en ocasiones se ha adoptado sin analizar sus implicancias identitarias. Este artículo analiza los resultados de una investigación referida a la implementación de un proyecto de formación por competencias. El análisis interpretativo de una muestra intencionada de registros ha sido la metodología empleada para contrastar las representaciones que los futuros profesores construyen sobre su labor, las competencias y los modelos profesionales que la orientan. Los resultados muestran las fracturas entre el proyecto y los significados construidos. FRACTURES OF THE IDENTITY IN THE FUTURE TEACHERS EDUCATION BY COMPETENCY-BASED: ANALYSIS OF AN EXPERIENCE Abstract: The competence based approach has become a real challenge for authorities and institutions working on improving the performance and formation of future teachers when implemented without analyzing the consequences in the professional identity. This paper reviews the results obtained in the application of an institutional project to strengthen the practical formation (practicum) based on the identification and inclusions of competences. A qualitative approach and the interpretation analysis of a sample of journals has been the methodology used to obtain and compare the representations of pre service teachers around their job, as well as, the abilities shown, and the professional approaches which influence their performance. The results allow to demonstrate breaks between the definitions of the project and the meaning constructed. Finally, emerging from the results, the bases of this proposal are discussed and some advices to solve and comprehend these difficulties are presented.